Modern sport science: from stagnation to new development paradigm - Lubysheva, L. I. (Theory and Practice of Physical Culture, 2017)
Modern Russian physical education system appears to be still largely limited by apologetics of the past theories and concepts. This situation effectively conserves the scientific progress by keeping in check the emerging potentially productive ideas and concepts. In the context of the modern initiatives to reform the national sport system and practices, the sector critically needs new practical approaches to the research process design and management in the national physical culture and sports sector to facilitate innovative processes, integrate new knowledge bases and employ them within the modern sport science development logics. This integrated knowledge, in our opinion, could be systematised by kinesiology as a system of research approaches to explore the human cognitive resource development mechanisms.